Tuning the Conduction Band Potential of Bi‐based Semiconductors Using a Combination of Organic Ligands. Issue 3 (10th December 2020) - Lei, Longfei; Han, Liuyuan; Wang, Jiajia; Liu, Yuanyuan; Wang, Zeyan; Wang, Peng; Zheng, Zhaoke; Cheng, Hefeng; Dai, Ying; Huang, Baibiao
Abstract: Most Bi‐based semiconductors are incapable of photocatalytic reduction reaction from a thermodynamic view, owing to relatively positive conduction band potentials ( E CB ). Here, a novel Bi‐based metal–organic framework (Bi‐MBA, MBA=4‐mercaptobenzoic acid) with excellent photocatalytic reduction activities is developed. The E CB of Bi‐MBA locates at −1.38 eV, which is able to efficiently reduce O2, Cr VI and CO2 . Theoretical calculations reveal the significant contribution of organic ligand (MBA) to the conduction band. Our results provide an effective route to improve the photocatalytic reduction activities of Bi‐based photocatalysts. Abstract : Long chain, multi‐purpose : A novel Bi‐based metal‐organic framework with a long chain structure of Bi2 S4 is reported. The combination of organic ligand can significantly upshift the conduction band potential of Bi‐based semiconductors to achieve photocatalytic reduction of O2, Cr (VI) and CO2 .